2023
DOI: 10.1039/d2sc06933d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and bonding patterns in heterometallic organometallics with linear Ln–Pd–Ln motifs

Abstract: Complexes with short intermetallic distances between transition metal fragments and lanthanide (Ln) fragments are fascinating objects of study, owing to the ambiguity of the nature of the interaction. The addition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The first example of RE–TM (transition metal) bonding interaction was reported by Beletskaya and co-workers in 1990, which was stabilized by a cyclopentadienyl skeleton . Previously studies have shown that ligands play critical roles in the stabilization of species with M–M bonds. According to the Hard–Soft Acid–Base theory, nitrogen–phosphorus ligands have been widely used in the construction of species with RE–M bonds, in which the N atom is a hard base which could coordinate with RE centers, while the P atom is a soft base, which could coordinate with TMs …”
Section: Introductionmentioning
confidence: 99%
“…The first example of RE–TM (transition metal) bonding interaction was reported by Beletskaya and co-workers in 1990, which was stabilized by a cyclopentadienyl skeleton . Previously studies have shown that ligands play critical roles in the stabilization of species with M–M bonds. According to the Hard–Soft Acid–Base theory, nitrogen–phosphorus ligands have been widely used in the construction of species with RE–M bonds, in which the N atom is a hard base which could coordinate with RE centers, while the P atom is a soft base, which could coordinate with TMs …”
Section: Introductionmentioning
confidence: 99%